2013
DOI: 10.2139/ssrn.2221299
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Concepts and Typology – An Evolutionary Discussion

Abstract: This paper is devoted to the analysis of evolution of innovation concepts, aspect and types. First emergence and evolution of different aspects and concepts of innovation are analysed, then the development of innovation concepts from a historical perspective and finally an overview given of types of innovation classifications developed in the literature. Surrounding this different definitions of innovation are described and analyzed in detail. The main goal of the article is to define the trend of development … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 153 publications
(106 reference statements)
0
42
0
2
Order By: Relevance
“…It can be categorized as all of the scientific, technological, financial, and commercial activity necessary to create, implement and develop new financial markets with improved financial assets (OECD 2004). Innovation not only considers the creation of a new thing but also acts as the panacea for prolonged economic problems (Kotsemir and Abroskin 2013). Schumpeter (1912) indicated that innovation can take place in the form of a new product, process, market, raw material, a method of distribution, or organizational structure.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…It can be categorized as all of the scientific, technological, financial, and commercial activity necessary to create, implement and develop new financial markets with improved financial assets (OECD 2004). Innovation not only considers the creation of a new thing but also acts as the panacea for prolonged economic problems (Kotsemir and Abroskin 2013). Schumpeter (1912) indicated that innovation can take place in the form of a new product, process, market, raw material, a method of distribution, or organizational structure.…”
Section: Theoretical Literaturementioning
confidence: 99%
“…Schumpeter defined innovation [1] as the setting up of a new production function, to denote the application of new ideas to the production process. Several authors [2][3][4] state that innovation is in the center of economic change. While radical innovations shape big changes in the world, incremental innovations fill in the process of change continuously.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation nowadays is not simply the "creation of something new" but also a panacea for the solution of a board range of problems. The term "innovation" is more and more often used -very frequently by policymakers, marketing specialists, advertising specialist and management consultants -not as a strictly scientific concept but as a metaphor, political promise, slogan or a buzzword (Kotsemir & Abroskin, 2013).…”
Section: Introductionmentioning
confidence: 99%